Correction: Synthesis and evaluation of nuciferine and roemerine enantiomers as 5-HT2 and α1 receptor antagonists. Issue 3 (7th March 2018) - Heng, Hui Li; Chee, Chin Fei; Chin, Sek Peng; Ouyang, Yifan; Wang, Hao; Buckle, Michael J. C.; Herr, Deron R.; Paterson, Ian C.; Doughty, Stephen W.; Abd. Rahman, Noorsaadah; Chung, Lip Yong
Abstract : Correction for 'Synthesis and evaluation of nuciferine and roemerine enantiomers as 5-HT2 and α1 receptor antagonists' by Hui Li Heng et al., Med. Chem. Commun., 2018, DOI: 10.1039/c7md00629b.